2014
DOI: 10.1186/s12920-014-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

High throughput exome coverage of clinically relevant cardiac genes

Abstract: BackgroundGiven the growing use of whole-exome sequencing (WES) for clinical diagnostics of complex human disorders, we evaluated coverage of clinically relevant cardiac genes on WES and factors influencing uniformity and depth of coverage of exonic regions.MethodsTwo hundred and thirteen human DNA samples were exome sequenced via Illumina HiSeq using different versions of the Agilent SureSelect capture kit. 50 cardiac genes were further analyzed including 31 genes from the American College of Medical Genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Additionally, although the study was not designed to allow direct comparison of different sequencing methods, the rate of causative mutations in cases screened using either the most sensitive technique (MiSeq targeted sequencing, in which exons with <20-fold coverage were individually resequenced using Sanger sequencing) or WES, was similar and supported our conclusion that approximately 40% cases are unsolved. Previous studies have also reported considerable variability in uniformity and depth of coverage across the exome, and these data, together with our sequencing depth analysis, highlight a limitation of targeted sequencing, which may impact and limit variant identification (33). High-depth, whole-genome sequencing can improve exon coverage and the advent of recent sequencing technologies (such as the Illumina X10 system) makes this possible at large scale.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Additionally, although the study was not designed to allow direct comparison of different sequencing methods, the rate of causative mutations in cases screened using either the most sensitive technique (MiSeq targeted sequencing, in which exons with <20-fold coverage were individually resequenced using Sanger sequencing) or WES, was similar and supported our conclusion that approximately 40% cases are unsolved. Previous studies have also reported considerable variability in uniformity and depth of coverage across the exome, and these data, together with our sequencing depth analysis, highlight a limitation of targeted sequencing, which may impact and limit variant identification (33). High-depth, whole-genome sequencing can improve exon coverage and the advent of recent sequencing technologies (such as the Illumina X10 system) makes this possible at large scale.…”
Section: Discussionsupporting
confidence: 58%
“…CH severity is classified according to European Society for Paediatric Endocrinology criteria on the basis of serum fT4 levels; severe, <5, moderate 5 to <10, and mild >10 pmol/liter, respectively (33) and pathogenicity is predicted according to American College of Medical Genetics guidelines (34). A schematic of the TG protein illustrates the position of the mutations relative to the key structural domains of TG including the repetitive type 1, 2, and 3 cysteine-rich regions, acetylcholinesterase homology (ACHE-like) domain and hormonogenic domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 With the known phenotypic overlap among CTDs and the sometimes imperative need to provide better counseling and guide clinical monitoring and intervention, NGS panels have been designed to explore simultaneously several genes known to cause different CTDs. 16,17 Including patients who had both NGS panels and conventional Sanger sequencing studies, molecular genetic studies for possible CTDs were performed in only 9% of patients. When those patients thought to have AoD caused by BAV or other conotruncal heart defects were excluded, the proportion of patients who underwent such studies was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported considerable variability in the coverage of known cardiac genes depending on the types of sequence capture kit and depth of sequencing used. 47 Sequence capture is the process of enrichment of selected genomic regions from whole genomic DNA and is required to capture the coding regions of the genome when exome sequencing is performed.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%